K-variant BCHE and pesticide exposure: Gene-environment interactions in a case–control study of Parkinson's disease in Egypt. Issue 1 (December 2018) - Rösler, Thomas; Salama, Mohamed; Shalash, Ali; Khedr, Eman; El-Tantawy, Abdelhalim; Fawi, Gharib; El-Motayam, Amal; El-Seidy, Ehab; El-Sherif, Mohamed; El-Gamal, Mohamed; Moharram, Mohamed; El-Kattan, Mohammad; et al.
Abstract Pesticide exposure is associated with increased risk of Parkinson's disease (PD). We investigated in Egypt whether common variants in genes involved in pesticide detoxification or transport might modify the risk of PD evoked by pesticide exposure. We recruited 416 PD patients and 445 controls. Information on environmental factors was collected by questionnaire-based structured interviews. Candidate single-nucleotide polymorphisms (SNPs) in 15 pesticide-related genes were genotyped. We analyzed the influence of environmental factors and SNPs as well as the interaction of pesticide exposure and SNPs on the risk of PD. The risk of PD was reduced by coffee consumption [OR = 0.63, 95% CI: 0.43–0.90, P  = 0.013] and increased by pesticide exposure [OR = 7.09, 95% CI: 1.12–44.01, P  = 0.036]. The SNP rs1126680 in the butyrylcholinesterase geneBCHE reduced the risk of PD irrespective of pesticide exposure [OR = 0.38, 95% CI: 0.20–0.70, P  = 0.002]. The SNP rs1803274, defining K-variantBCHE, interacted significantly with pesticide exposure (P  = 0.007) and increased the risk of PD only in pesticide-exposed individuals [OR = 2.49, 95% CI: 1.50–4.19, P  = 0.0005]. The K-variantBCHE reduces serum activity of butyrylcholinesterase, a known bioscavenger for pesticides. Individuals with K-variantBCHE appear to have an increased risk for PD when exposed to pesticides.